589 Comparative Study on the Topspin and Retopspin Execution Biomechanics in Female Cadets (Balneo and PRM Research Journal, 2024)
Abstract: Background: Many high-performance table tennis specialists and athletes may wonder if there are differences between the two most used technical-tactical elements in attack and which are these, given that their name and the biomechanical execution are characterized by approximately similar landmarks. Knowing the differences between the two technical elements, we will be able to understand and streamline the execution biomechanics. The biomechanical analysis of a large number of athletes on the three stages of execution and speed developed at the time of using topspin or retopspin (counter loop). Methods: The research engaged several 10 Romanian sportswomen involved in high-performance table tennis, with ages between 13-15 years old. Goal: Identify the distinctive biomechanical features between the two elements and the speed needed for execution optimization. Results: For data collection, analysis, and interpretation, we used Excel, IBM SPSS Statistics 23, analysis software Dartfish 360s, and for the technical-tactical expression level ‘’Topspin with crosswise retopspin, forehand, and backhand’’, “Butterfly” and “Multiball training”. Conclusions (4): The preparation of the forehand topspin hit requires an angle of 146.36 degrees(0) and 0.36 seconds(s) for the entire execution, while the forehand retopspin is 134.20 and 0.31 s, backhand topspin hit requires an angle of 920 and 0.32 s, while the retopspin  86,720 and 0.26 s for the entire execution.